1994
DOI: 10.1118/1.597339
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy measurements of a high dose rate Ir‐192 source in air and in polystyrene

Abstract: Anisotropy measurements in air and in polystyrene were performed for a Nucletron microSelectron 10 Ci Ir-192 source. TLD rods of similar sensitivity (+/- 3%) were placed on a semicircle around the source center which had been precisely localized by either radiographic means or direct measurement. The anisotropy, expressed as a ratio of TLD reading at a given angle relative to the longitudinal source axis, over the reading at 90 degrees, was measured for distances between 1 and 10 cm from the source center. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…As shown in Figure 4c, a distinct F(r, θ ) differences were not noted in the lung phantom. These results are similar to the air measurements reported by Muller-Runkel and Cho [7].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure 4c, a distinct F(r, θ ) differences were not noted in the lung phantom. These results are similar to the air measurements reported by Muller-Runkel and Cho [7].…”
Section: Resultssupporting
confidence: 92%
“…Researchers found that the multi-dimensional dose distributions could be acquired once the former was determined [5], [6], [7], [8], [9]. Mishra et al used a 0.147 cm 3 ionization chamber to measure 192 Ir anisotropy function in a water phantom [10].…”
Section: Introductionmentioning
confidence: 99%
“…7 The holes to accommodate TLD rods were distributed on both sides of the source axis. This design has the following advantages: (i) facilitating the craft in phantom manufacture, (ii) reducing the interaction of TLDs at the position in different radius, and (iii) improving the efficiency by exposing TLDs in 2 radii through one exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, its active center is not identical to the geometrical center. The active center was found by dosimetry and radiography methods, both of which were similar with that described by Muller-Runkel et al 7 Dosimetry method. A same polystyrene plate as the phantom was prepared, except for the position of holes for TLD rods.…”
Section: Location Of the Active Centermentioning
confidence: 96%
“…The same catheters were used throughout our experiments and the inhomogeneity due to these catheters was not taken into account. 192 Ir source from HDR machine was allowed to dwell at a point such that the center of the chamber, and the center and transverse axis of the source[1214] were collinear. A 2 cm 2 cm× 2 cm hole/slot was made in the wax phantom between the ion chamber and source dwell point to accommodate tissues of different thicknesses (0.5 cm, 1.0 cm, 1.5 cm and 2.0 cm).…”
Section: Methodsmentioning
confidence: 99%